2018
DOI: 10.2478/pjst-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Correlations Between Gross and Fine Motor Skills, Physical Fitness, and the Level of Functioning in Schoolchildren with Intellectual Disabilities

Abstract: Introduction. Physical fitness affects motor and intellectual development. Having a wide range of motor skills makes it possible to learn about the surrounding world and expand one’s knowledge. In the case of persons with intellectual disabilities, mastering gross and fine motor skills is the core of their development and functioning in society. The aim of the study was to analyse the relationship between physical fitness, gross and fine motor skills, and the level of functioning in schoolchildren with intelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…These outcomes align with other studies that have shown significant correlations between fine and gross motor abilities in school students. 6,8,44,45 Results highlight that regular motor coordination and cardiorespiratory fitness screening programs in schools must be implemented and integrated into existing health programs. 46 A potential limitation of this study is that we used a convenience sample and a sample size calculation was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes align with other studies that have shown significant correlations between fine and gross motor abilities in school students. 6,8,44,45 Results highlight that regular motor coordination and cardiorespiratory fitness screening programs in schools must be implemented and integrated into existing health programs. 46 A potential limitation of this study is that we used a convenience sample and a sample size calculation was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Gerakan merupakan bagian tak terpisahkan dari keberadaan manusia, dan aktivitas fisik sudah terjadi pada hari-hari pertama kehidupan (Skowroński et al, 2018). Permainan tradisional bakiak merupakan permainan yang mudah dijumpai disekitar tempat tinggal, berbeda dengan permainan modern yang lebih banyak menggunakan biaya serta membuat anak menjadi malas melatih otot-otot besar, serta hanya merusak indera penglihatan.…”
Section: Pendahuluanunclassified
“…Manfaat perkembangan motorik, anak memperoleh keterampilan yang semakin kompleks. Pengembangan keterampilan motorik yang tepat merupakan sumber kesenangan, kepuasan, dan kegembiraan bagi mereka (Skowroński et al, 2018). Studi tentang interaksi antara keterampilan motorik kasar dan halus penting untuk mengidentifikasi strategi baru untuk meningkatkan pembelajaran motorik selama masa kanak-kanak (Sorgente et al, 2021).…”
Section: Pendahuluanunclassified
“…In his theory of motor development, Gallahue examined motor development in four periods. These periods are the period of reflexive movements, the period of primitive movements, the period of basic movements, and the period of sports movements ( Skowroński et al, 2018 ). Preschool and school periods are the periods of basic movements of children.…”
Section: Introductionmentioning
confidence: 99%